Characterization of the 2010-decade historical drought in Paraiba do Sul River Basin, Sao Paulo State, Brazil - Neves, Anderson de Oliveira; Nogueira Vilanova, Mateus Ricardo [UNESP] (Assoc Brasileira Engenharia Sanitaria Ambiental, 2021)
The Paraiba do Sul River Basin was affected by one of the most severe drought periods in its recent history, during the years 2013 to 2015, which resulted in several consequences for the management of its water resources. This article aims to contribute to the understanding of this historical event in the sao Paulo Stretch of the Paraiba do Sul River Basin, through the calculation and analysis of the standardized precipitation index (SPI). SPI was calculated for the time scales of 1, 3, 6, and 12 months, for 22 rainfall stations located in the study area. The results showed that the drought occurred between 2013 and 2014 was one of the most severe ever recorded, and that the summer of 2014 was the critical period in terms of reduction of regional rainfall. This drought impacted the storage and regularization capacity of the main reservoir of the region, the Paraibuna Reservoir. Although the peak of the water crisis occurred mainly due to the 2013/2014 drought, it was found that it was influenced by the cumulative effect of a previous dry period, that occurred since the beginning of the year of 2011. This result reinforces the importance of multiannual planning for the operation of the Paraiba do Sul River Basin Hydraulic System.
Keywords: rainfall; standardized precipitation index; water shortage; Paraiba do Sul River